A remote smartphone cognitive testing battery for frontotemporal dementia: Completion rate, reliability, and validity. (31st December 2021) - Staffaroni, Adam M.; Taylor, Jack C; Clark, Annie L; Heuer, Hilary W.; Forsberg, Leah K.; Bahl, Riley; Manoochehri, Masood; Vento, Stephanie; Bajorek, Lynn P.; Ong, Elise; You, Michelle; Boeve, Bradley F.; et al.
Abstract: Background: In preparation for treatment trials in frontotemporal dementia (FTD), sensitive assessments to detect early clinical deficits and track longitudinal changes are needed. Remote digital data collection using smartphones may improve sensitivity to detect and follow abnormalities by allowing novel methods of data capture and more frequent assessments. Furthermore, remote evaluations can reduce patient and staff burden. Despite these benefits, little is known about the reliability and validity of self‐administered cognitive testing completed on smartphones. Method: We investigated self‐administered smartphone cognitive tests from the ALLFTD Mobile App in a mixed sample of 45 participants, including 10 functionally intact older adults, 24 participants from families harboring pathogenic FTD mutations (asymptomatic n=14; mildly symptomatic n=10;), and 11 symptomatic FTD‐spectrum participants. A subset (n=15) was missing CDR®+NACC‐FTLD data but consensus diagnoses were available. Participants were asked to complete five tests that were repeated three times over eight days. Tests included versions of N‐back, Stroop, Flanker, and Go/No‐Go paradigms, and an adaptive spatial working memory test. Reliability was assessed using split‐half reliability (first testing session, 100 simulations) and intraclass correlations (ICC) across the three testing sessions. Linear models were fitted to evaluate the association of test performance with age and disease severity (CDR®+NACC‐FTLD Global and Box Scores), covarying for sex and education level. Models evaluating age associations excluded symptomatic participants. Result: Participants completed 72.4% of available instruments. Split‐half reliability (range: 0.76 to 0.97) and ICCs (0.70 to 0.92) suggested adequate‐to‐excellent internal consistency and test‐retest reliability. Across the five tests, negative associations were observed with CDR®+NACC‐FTLD Box Scores (ßs = ‐0.24 to ‐0.77), and in clinically asymptomatic individuals, negative associations were observed with age (ßs = ‐0.43 to ‐0.88). Performance on all measures was worse in symptomatic participants compared to asymptomatic (p‐values<.05). Mildly symptomatic cases (CDR®+NACC‐FTLD=0.5) performed worse on Stroop, Flanker, and spatial working memory than asymptomatic participants (p‐values<.03). Flanker and Stroop tasks consistently showed the strongest reliability and validity findings. Conclusion: Smartphone adaptations of common neuropsychological tests produced promising preliminary results. Strong associations with disease severity and age suggest these metrics may be valid for detecting clinically relevant cognitive changes, even in mildly symptomatic FTD.